2016
DOI: 10.1093/pcp/pcw109
|View full text |Cite
|
Sign up to set email alerts
|

Role of Transcription Factor HAT1 in ModulatingArabidopsis thalianaResponse toCucumber mosaic virus

Abstract: Arabidopsis thaliana homeodomain-leucine zipper protein 1 (HAT1) belongs to the homeodomain-leucine zipper (HD-Zip) family class II that plays important roles in plant growth and development as a transcription factor. To elucidate further the role of HD-Zip II transcription factors in plant defense, the A. thaliana hat1, hat1hat3 and hat1hat2hat3 mutants and HAT1 overexpression plants (HAT1OX) were challenged with Cucumber mosaic virus (CMV). HAT1OX displayed more susceptibility, while loss-of-function mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…HAT1 interacts with BES1, a central regulator in BR signaling pathway, and functions as a BES1 co-repressor to inhibit BR-repressed genes and thus optimizes BR-regulated plant growth [ 30 ]. In addition, HAT1 acts as a repressor in plant defense response to CMV infection [ 31 ]. Thus, HAT1 may function as a transcriptional regulator to modulate plant growth and stress response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAT1 interacts with BES1, a central regulator in BR signaling pathway, and functions as a BES1 co-repressor to inhibit BR-repressed genes and thus optimizes BR-regulated plant growth [ 30 ]. In addition, HAT1 acts as a repressor in plant defense response to CMV infection [ 31 ]. Thus, HAT1 may function as a transcriptional regulator to modulate plant growth and stress response.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that HAT1 is a substrate of BIN2 (BRASSINOSTEROID-INSENSITIVE 2) kinase and appears to function redundantly with other family members such as HAT3 to positively mediate BR responses [ 30 ]. HAT1 was also reported to participate in anti-CMV defense response in Arabidopsis and negatively regulates this process [ 31 ]. Collectively, these studies indicate that HAT1 is involved in the complex signaling and transcriptional networks coordinating plant growth and stress response.…”
Section: Introductionmentioning
confidence: 99%
“…(1) The negative regulators of plant defenses, such as rgs-CaM that inhibited RNA silencing through repressing the transcription level of RDR6 and degrading the SGS3 protein via autophagy , and homeodomain leucine zipper protein 1 (HAT1) and its related genes HAT2 and HAT3, whose mutation conferred loss-of-susceptibility to CMV infection by accumulating high levels of SA and jasmonic acid (JA) (Zou et al, 2016).…”
Section: The Promising Host Susceptibility Genes For Antiviral Enginementioning
confidence: 99%
“…Interestingly, HAT1 has also been linked to brassinosteroid (BR) signaling pathway. Recent work has demonstrated that HAT1, apart from its role in auxin-regulated cotyledon development (Figure 3), in BR-mediated growth responses [95], in GA signaling, and in viral defense response in a manner dependent on salicylic acid (SA) [101], it also negatively regulates, redundantly with HAT3, ABA-mediated drought responses through suppression of ABA biosynthesis and signaling [102]. Interestingly, the effect of ATHB17 on seedling growth in the presence of ABA is stage-specific.…”
Section: Hd-zips IImentioning
confidence: 99%